Client attendance measures in counselling psychology trainees. Issue 1 (27th June 2020) - Meier, Scott T.
Abstract: Counselling supervisors and educators have yet to reach a consensus about standard measures for evaluating the performance of graduate student therapists. Compared to self‐reports and rater judgements, client attendance records provide low‐inference behavioural data partially reflective of clients' engagement with therapists. This naturalistic study evaluates client attendance data using archival records of 92 doctoral students in beginning and advanced counselling practica who produced data for 771 clients, 3, 949 scheduled sessions and 3, 186 attended sessions. Providing evidence of the sample representativeness for clinicians, results indicated that the mean number of sessions attended per client for student therapists (5.65) was very similar to that reported in the literature for outpatient therapists (<6). As expected because of structural differences in client assignment, beginning and advanced students evidenced statistically significant differences on attendance variables such as number of clients and scheduled sessions. In contrast, attendance ratios were equivalent across counsellor experience, suggesting that these individual difference variables could be useful for evaluation of therapist competencies related to client engagement.